Firms' export dynamics: experience vs. size - Antoine Berthou; Vincent Vicard (European Central Bank (ECB), 2013)
This paper provides evidence about the impact that size and experience in exporting have on firms' dynamics, a critical input in models of firms' dynamics. The analysis uses a census of French exports by firm-destination-product over the period 1994-2008 with a monthly frequency. We first uncover a large calendar year bias: the growth of exporters between the first and the second year of export is biased upwards because new exporters may start exporting late during the year. This incomplete calendar year reduces export revenue by 32% on average for the first year of export. We then show that, controlling for size, export experience is negatively related to net growth of exports for surviving exporters. Controlling for export experience, the relationship between average size and net growth of exports shows no systematic pattern. Finally, churning in foreign markets is decreasing with export experience and (sharply) with size.
Keywords: F14; 330; international trade